12/15-lipoxygenase orchestrates murine wound healing via PPARγ-activating oxylipins acting holistically to dampen inflammation - Christopher P. Thomas; Victoria J. Tyrrell; James J. Burston; Sam R. C. Johnson; Maceler Aldrovandi; Jorge Alvarez-Jarreta; Rossa Inglis; Adam Leonard; Lydia Fice; Jeremie Costales; Antonio Vidal-Puig; Majd Protty; et al. (Proceedings of the National Academy of Sciences, 2025)
12/15-lipoxygenase (12/15-LOX, Alox15 ) generates bioactive oxygenated lipids during inflammation, however its homeostatic role(s) in normal healing are unclear. Here, the role of 12/15-LOX in resolving skin wounds was elucidated, focusing on how its lipids act together in physiologically relevant amounts. In mice, wounding caused acute appearance of 12/15-LOX-expressing macrophages and stem cells, coupled to early generation of ~12 monohydroxy-oxylipins and enzymatically oxidized phospholipids (eoxPL). Alox15 deletion increased collagen deposition, stem cell/fibroblast proliferation, IL6/pSTAT3, pSMAD3, and interferon (IFN)-γ levels. Conversely, CD206 expression, F480+ cells, and MMP9 and MMP2 activities were reduced. Alox15 −/− skin was deficient in PPARγ/adiponectin activity. Furthermore, while pro-inflammatory genes were upregulated as normal during wounding, many including Il6, Il1b, ccl4, Cd14, Cd274, Clec4d, Clec4e, Csf3, Cxcl2, and miR-21 failed to revert to baseline during healing, indicating disruption of PPARγ’s anti-inflammatory brake on NLRP3/inflammasome and TGF-β signaling. Reconstituting Alox15 −/− wounds with a physiological mixture of Alox15 -derived primary oxylipins generated by healing wounds restored MMP and dampened collagen deposition. The oxylipin mixture activated the PPARγ response element in vitro, while in vivo, its coactivator, Helz2 , was significantly upregulated as well as several fatty acid and prostaglandin PPARγ ligands. Additional inflammatory and proliferative gene networks impacted by Alox15 −/− included Elf4, Cebpb , and Tcf3. In summary, 12/15-LOX generates abundant monohydroxy oxylipins that act together via PPARγ. The identification of multiple gene alterations reveals several targets for treating nonhealing wounds. Our studies demonstrate that 12/15-LOX oxylipins act in concert, dampening inflammation in vivo, revealing the need to consider lipid signaling holistically.